Novel Insights for Metabiotics Production by Using Artisanal Probiotic Cultures - Marina Pihurov (MDPI AG, 2021)
Wild probiotic consortia of microorganisms (bacteria and yeasts) associated in the artisanal cultures’ microbiota (milk kefir grains, water kefir grains and kombucha) are considered valuable promoters for metabiotics (prebiotics, probiotics, postbiotics and paraprobiotics) production. The beneficial effects of the fermented products obtained with the artisanal cultures on human well-being are described by centuries and the interest for them is continuously increasing. The wild origin and microbial diversity of these above-mentioned consortia give them extraordinary protection capacity against microbiological contaminants in unusual physico-chemical conditions and unique fermentative behaviour. This review summarizes the state of the art for the wild artisanal cultures (milk and water kefir grains, respectively, kombucha—SCOBY), their symbiotic functionality, and the ability to ferment unconventional substrates in order to obtain valuable bioactive compounds with in vitro and in vivo beneficial functional properties. Due to the necessity of the bioactives production and their use as metabiotics in the modern consumer’s life, artisanal cultures are the perfect sources able to biosynthesize complex functional metabolites (bioactive peptides, antimicrobials, polysaccharides, enzymes, vitamins, cell wall components). Depending on the purposes of the biotechnological fermentation processes, artisanal cultures can be used as starters on different substrates. Current studies show that the microbial synergy between bacteria—yeast and/or bacteria—offers new perspectives to develop functional products (food, feeds, and ingredients) with a great impact on life quality.